“Improving The Students’ Writing Narrative Text by Applying Cooperative Learning Type Student Teams Achievement Divisions (STAD)” - Enry Pratama Poetra; Devi Sansan Gustiana; Iman Santoso (IKIP Siliwangi, 2019)
This research aimed to analyze the student teams achievement divisions (STAD) technique of cooperative learning approach to improve writing narrative text. This study was a quantitative method and pre-experimental design in this research,the subject of the study was implemented in RPL 1 class tenth grade students of SMK Mahardhika Batujajar west Bandung in the 2018- 2019 academic years as sample. The data were obtained from several sources including the data analysis of pretestand posttest, then the dataanalysis of descriptive statistics and N-Gain. The results of this reserach that student teams achievement division(STAD) technique is effective in teaching writing narrative text data from classroom observation and students texts show the improvement in students writing skill in writing narrative text. The students write a good narrative text with clear generic structures and can understood the linguistic. It could be seen from the average of posttest results was 78.87 and the data avarege of pretest results in class research was 41.17 the difference score pretest and postest showed the STAD technique can improve students ability writing narrative text.Key Words: Cooperative Learning, STAD, Writing, Narrative text.